2022
DOI: 10.1186/s13287-022-03042-4
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Follistatin-like 1 guarantees the immunomodulatory properties of mesenchymal stem cells during liver fibrotic therapy

Abstract: Background Mesenchymal stem cell (MSC) therapy has been shown to be a promising option for liver fibrosis treatment. However, critical factors affecting the efficacy of MSC therapy for liver fibrosis remain unknown. Follistatin-like 1 (FSTL1), a TGF-β-induced matricellular protein, is documented as an intrinsic regulator of proliferation and differentiation in MSCs. In the present study, we characterized the potential role of FSTL1 in MSC-based anti-fibrotic therapy and further elucidated the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…also clarified that Fstl1 facilitates the immunosuppressive of MSCs on macrophages and guarantees the anti‐fibrotic effect of MSCs in liver fibrosis. [ 28 ] Fstl1 is highly expressed in activated HSCs, while Fstl1 knockdown effectively suppresses HSCs proliferation by the TGF‑ β 1/Smad3 signaling pathway. [ 29 ] In our study, Fstl1 was also highly expressed in cirrhosis and regulated by Kcnq1ot1 and miR‐374‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…also clarified that Fstl1 facilitates the immunosuppressive of MSCs on macrophages and guarantees the anti‐fibrotic effect of MSCs in liver fibrosis. [ 28 ] Fstl1 is highly expressed in activated HSCs, while Fstl1 knockdown effectively suppresses HSCs proliferation by the TGF‑ β 1/Smad3 signaling pathway. [ 29 ] In our study, Fstl1 was also highly expressed in cirrhosis and regulated by Kcnq1ot1 and miR‐374‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that human bone marrow-derived MSCs (BM-MSCs) transplantation rescued fulminant hepatic failure mice, as demonstrated by robust proliferation and trans-differentiation of functional hepatocytes and multiple immune cell lineages, including B cells, T cells, NK cells, DCs and macrophages [ 55 ]. Zheng et al [ 56 ] reported that Follistatin-like 1 (FSTL1) is essential for the immunosuppressive action of MSCs on inflammatory macrophages in liver fibrotic therapy. Knockdown of FSTL1 in MSCs significantly attenuated this property through inhibiting the downstream Janus kinase/STAT1/IDO pathway.…”
Section: Potential Mechanisms Of Mscs-based Therapy In Liver Diseasesmentioning
confidence: 99%
“…The transformed cells may be injected into the liver locally or intravenously to restore liver function or encourage liver regeneration [ 9 ]. The therapeutic effect of cell therapy has been extensively studied in animal models [ 10 , 11 ]. The first study on cell therapy was conducted in 1976 by Najarian, who transplanted allogeneic hepatocytes into a rat model of congenital enzyme deficiency disease via the portal vein [ 12 ].…”
Section: Introductionmentioning
confidence: 99%